Acceptor side-chain effects on the excited state dynamics of two-dimensional-like conjugated copolymers in solution - Huo, Ming-Ming; Hu, Rong; Yan, Wei; Wang, Yi-Tong; Chee, Kuan; Wang, Yong; Zhang, Jian-Ping (MDPI, 2017)
Excited state dynamics of two-dimensional-like conjugated copolymers PFDCN and PFSDCN based on alternating fluorene and triphenylamine main chains and malononitrile pendant acceptor groups with thiophene as π-bridge, have been investigated by using transient absorption spectroscopy. There is an additional conjugated –C=C– bond in PFDCN, which distinguishes it from PFSDCN. The lowest energy absorption band of each copolymer absorption spectrum is attributed to the π−π* transition with intramolecular charge-transfer, which has a lower fluorescence contribution than those of higher energy absorption bands. The optical excitation of either PFDCN or PFSDCN solution generates polaron pairs that then self-localize and evolve to a bound singlet exciton within a few picoseconds. Due to the additional conjugated –C=C– bond in the acceptor side-chain, PFDCN has a stronger intramolecular charge-transfer characteristic compared with PFSDCN, therefore exhibiting a longer self-localization time (7 ps vs. 3 ps for PFSDCN) and a shorter fluorescence lifetime (1.48 ns vs. 1.60 ns for PFSDCN).